Strategies to Overcome Heparins' Low Oral Bioavailability - Ana Rita Neves; Marta Correia-; Emília Sousa; Madalena Pinto (MDPI AG, 2016)
Even after a century, heparin is still the most effective anticoagulant available with few side effects. The poor oral absorption of heparins triggered the search for strategies to achieve oral bioavailability since this route has evident advantages over parenteral administration. Several approaches emerged, such as conjugation of heparins with bile acids and lipids, formulation with penetration enhancers, and encapsulation of heparins in micro and nanoparticles. Some of these strategies appear to have potential as good delivery systems to overcome heparin's low oral bioavailability. Nevertheless, none have reached the market yet. Overall, this review aims to provide insights regarding the oral bioavailability of heparin.